Magnetic spinel recoverable adsorbent and preparation method and application thereof

FeMn2O4 magnetic spinel adsorbent was prepared by mixing FeCl3, MnCl2 and NaOH aqueous solutions, which solved the problem of insufficient adsorption capacity of iron-based spinel, achieved efficient removal of Sb(III) in high-concentration antimony sewage, and passed through magnet Recycling realizes the reuse of adsorbents.

CN119140056APending Publication Date: 2024-12-17CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411540988.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing iron-based spinel adsorbent has limited adsorption capacity of trivalent antimony in water, and the preparation process is complicated, so it is impossible to effectively remove high concentrations of antimony-containing wastewater.

Method used

The FeMn2O4 magnetic spinel adsorbent was prepared by mixing FeCl3, MnCl2 and NaOH aqueous solutions, and after heating in water bath and vacuum drying at 300-600°C, which had strong adsorption ability and easy recovery.

Benefits of technology

The prepared magnetic spinel adsorbent can reach an adsorption rate of 99.41% within 20 minutes. It has a high adsorption capacity for Sb(III) of 600mg/L, and can still maintain effective removal after recovery by magnets. It is suitable for high concentrations. Antimony wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140056A_ABST
    Figure CN119140056A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic spinel recoverable adsorbent and a preparation method and application thereof, and the method comprises the following steps: (S1) fully mixing a FeCl3 aqueous solution, a MnCl2 aqueous solution and a NaOH aqueous solution to form a suspension; and (S2) putting the turbid liquid obtained by mixing in the step (S1) into a water bath kettle at 97 DEG C, heating for 120 minutes, repeatedly washing the obtained slurry with absolute ethyl alcohol and deionized water, removing residual alkaline substances, drying the obtained particles in a vacuum drying oven at 100 DEG C for 3-5 hours, sufficiently grinding, putting into a tubular furnace, and annealing for 180 minutes at 300-600 DEG C at a heating rate of 10 DEG C / min to obtain the FeMn2O4 magnetic adsorbent. The magnetic spinel recoverable adsorbent disclosed by the invention is high in adsorption capacity, and when the concentration of an antimony-containing solution is 600mg / L, the maximum adsorption capacity of FeMn2O4 is measured to be 2674.49 mg / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a magnetic spinel recyclable adsorbent, in particular to a magnetic spinel recyclable adsorbent and a preparation method and application thereof. Background Art

[0002] Waste ore, waste slag and production wastewater generated during antimony mining and smelting lead to abnormal release of antimony and other heavy metal elements, which enter the soil of the mining area through infiltration, diffusion, surface runoff and other pathways, causing heavy metal pollution and threatening the safety of the groundwater environment. The content of antimony in uncontaminated environmental media is usually less than 1μg / L, but human pollution often causes the antimony concentration level to exceed the natural level. In some antimony mines and their smelting areas, high background values ​​of antimony and abnormal geochemical behavior have appeared. Studies have found that both groundwater and surface water in abandoned antimony mining areas contain high concentrations of antimony, up to 9300μg / L. There are also varying degrees of antimony pollution in the water and soil around the mining area. Compared with the soil environment and the atmospheric environment, antimony in the water environment is more mobile and persistent. Antimony in the water environment can accumulate within a certain distance along the way without significant attenuation. After long-distance migration, it further poses a potential threat to human health through processes such as water and soil accumulation and plant and animal enrichment. Therefore, the control and remediation of antimony pollution in water bodies face strict requirements and severe challenges. The adsorption method has become the most ideal method for antimony removal because it is suitable for the removal of heavy metal ions and has the advantages of high efficiency, low cost and easy operation.

[0003] The molecular formula of spinel is AB2O4, where A is a divalent cation and B is a trivalent cation. Due to its chemical adsorption properties and stable structure, spinel is useful in dealing with heavy metal pollution such as Sb and Zn. However, common spinels such as MnFe2O4 and CuFe2O4 have an adsorption capacity of only 229.89 mg / L and 204.92 mg / L for Sb(III), which cannot effectively remove antimony-containing wastewater. The preparation process is also relatively complicated, and there are almost no reports on the reuse of this function. Therefore, the control and remediation of antimony pollution in water bodies face strict requirements and severe challenges, and there is an urgent need for a spinel adsorbent with strong adsorption capacity to fill the gap in dealing with heavy metal pollution.

[0004] The document "Study on the Adsorption Behavior and Mechanism of Spinel Ferrite in Removing Antimony from Water" (Guangdong Chemical Industry, Vol. 50, Issue 24, 2023) discloses a method for preparing spinel ferrite, which is: 5.0mmol FeCl3·6H2O and 2.5mmolMn(Ac)2·4H2O (or CuCl2, ZnCl2, NiCl2) are completely dissolved in 40mL ethylene glycol, and then 3.6g NaAc and 1.5g polyethylene glycol are added. After complete dissolution, pour into a 50mL high-pressure reactor and react at 200°C for 12h. After the reaction is completed, cool to room temperature, wash the product repeatedly with deionized water and anhydrous ethanol, and freeze-dry to obtain the corresponding ferrite. However, this method has a long reaction time and requires more complicated steps. In addition, for the adsorption capacity of the four spinels for antimony, when the initial concentration of Sb(III) reaches 230 mg / L, the adsorption capacity of MnFe2O4, ZnFe2O4, CuFe2O4 and NiFe2O4 for Sb(III) reaches the maximum, which are 196.94, 164.30, 180.72 and 145.69 mg / g respectively, that is, the size of the adsorption capacity meets the order of MnFe2O4>CuFe2O4>ZnFe2O4>NiFe2O4. It can be seen that the adsorption capacity of the four iron-based spinels is also relatively limited, and it is not possible to effectively remove high-concentration antimony-containing wastewater.

[0005] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0006] The purpose of the present invention is to provide a magnetic spinel recyclable adsorbent and a preparation method and application thereof, which solves the problem that the existing iron-based spinel has a relatively limited adsorption capacity. The magnetic spinel recyclable adsorbent prepared by the method of the present invention has a strong adsorption capacity for trivalent antimony in water, a fast removal speed, and is easy to recycle.

[0007] In order to achieve the above object, the present invention provides a method for preparing a magnetic spinel recyclable adsorbent, the method comprising the following steps:

[0008] (S1) the FeCl3 aqueous solution, the MnCl2 aqueous solution and the NaOH aqueous solution are fully mixed to form a suspension;

[0009] (S2) placing the suspension obtained by mixing in step (S1) in a 97°C water bath and heating it for 120 min, repeatedly washing the obtained slurry with anhydrous ethanol and deionized water to remove residual alkaline substances, and drying the obtained particles in a vacuum drying oven at 100°C for 3 to 5 hours. After being fully ground, placing them in a tubular furnace, and annealing them at 300 to 600°C for 180 min at a heating rate of 10°C / min to obtain a FeMn2O4 magnetic adsorbent.

[0010] Preferably, the concentration of the FeCl3 aqueous solution is 0.2 mol / L; the concentration of the MnCl2 aqueous solution is 0.4 mol / L; and the concentration of the NaOH aqueous solution is 10.00-4.29 mol / L.

[0011] Preferably, the concentration of the NaOH aqueous solution is 6 mol / L.

[0012] Preferably, the annealing temperature is 400-600°C.

[0013] The second object of the present invention is to provide a recyclable magnetic spinel adsorbent obtained by the preparation method.

[0014] The third object of the present invention is to provide the magnetic spinel recyclable adsorbent in adsorbing Sb 3+ In the application, under the condition of pH 4 or ≥7, the magnetic spinel recyclable adsorbent is effective for Sb 3+ Adsorption.

[0015] Preferably, the adsorption time is 5 hours; or / and the adsorption is carried out on a shaker at 180 rpm; or / and the adsorption is carried out at room temperature.

[0016] Preferably, the adsorption is carried out at a pH of 4, 7, 8, 9 or 10.

[0017] Preferably, the Sb 3+ The initial concentration is 460~620mg / L.

[0018] More preferably, the Sb 3+ The initial concentration was 600 mg / L.

[0019] Preferably, the magnetic spinel recyclable adsorbent is recovered by a magnet, repeatedly rinsed with deionized water, dried, and reused.

[0020] The magnetic spinel recyclable adsorbent and its preparation method and application of the present invention solve the problem of limited adsorption capacity of existing iron-based spinels and have the following advantages:

[0021] (1) The preparation method of the present invention has rapid reaction and simple operation. The reaction can be successfully completed in a boiling water bath for 2 hours. The control method is easy. After drying, annealing treatment is performed for 3 hours to obtain the finished product.

[0022] (2) The magnetic spinel recyclable adsorbent of the present invention has a strong adsorption capacity. When the concentration of the antimony-containing solution is 600 mg / L, the maximum adsorption capacity of FeMn2O4 is measured to be 2674.49 mg / g;

[0023] (3) The magnetic spinel recyclable adsorbent of the present invention has a fast adsorption rate. Within 20 minutes, FeMn2O4 exhibits a relatively fast adsorption rate for Sb(III), and the adsorption capacity can reach 99.41% of the adsorption equilibrium capacity. All samples basically reach equilibrium within 60 minutes, and the adsorption amount of Sb(III) when reaching adsorption equilibrium is 891.31 mg / g.

[0024] (4) The magnetic spinel recyclable adsorbent of the present invention has good reusability and strong magnetism and can be easily recovered by a magnet. After recycling and passing through two cycles, FeMn2O4 can still effectively remove 600 mg / L of Sb(III), and the third cycle can still remove 72.89% of Sb in the solution. 3+ , which has important social and economic significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the XRD characterization diagram of the magnetic spinel recyclable adsorbent prepared in Examples 1 to 4 of the present invention.

[0026] Figure 2 This is a comparison chart of the adsorption capacity of FeMn2O4 for Sb(III) at four different annealing temperatures in Experimental Example 1 of the present invention.

[0027] Figure 3 It is the FeMn2O4 adsorption isotherm and the Langmuir and Freundlich adsorption isotherm model fitting diagram under 600℃ annealing in Experimental Example 1 of the present invention.

[0028] Figure 4 This is a graph showing the relationship between the solution pH and the antimony removal performance of FeMn2O4 under 600°C annealing in Experimental Example 1 of the present invention.

[0029] Figure 5 This is a diagram showing the effect of FeMn2O4 annealed at 600°C in removing antimony from actual water in a reuse experiment in Experimental Example 2 of the present invention. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0032] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0033] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.

[0034] Example 1

[0035] A magnetic spinel recyclable adsorbent, the preparation method of which comprises the following steps:

[0036] (S1) 2.703 g (10 mmol) of FeCl3·6H2O and 3.9582 g (20 mmol) of MnCl2·4H2O were dissolved in 50 mL of deionized water, respectively, and magnetically stirred for 20 to 60 min to obtain a 0.2 mol / L FeCl3 aqueous solution and a 0.4 mol / L MnCl2 aqueous solution; 12 g (300 mmol) of sodium hydroxide solid was added to 50 mL of deionized water to prepare a 6 mol / L NaOH aqueous solution; the three aqueous solutions were fully mixed to form a reddish brown suspension;

[0037] (S2) placing the suspension obtained by mixing in step (S1) in a 97°C water bath and heating it for 120 min, repeatedly washing the obtained slurry with anhydrous ethanol and deionized water to remove residual alkaline substances, and drying the obtained purple-black particles in a 100°C vacuum drying oven for 3 to 5 hours, and after being fully ground, placing them in a tubular furnace, and annealing them at 300°C for 180 min at a heating rate of 10°C / min to obtain a FeMn2O4 magnetic adsorbent.

[0038] Example 2

[0039] A magnetic spinel recyclable adsorbent, the preparation method of which is substantially the same as that of Example 1, except that:

[0040] In step (S2), FeMn2O4 magnetic adsorbent is obtained under an annealing temperature of 400°C.

[0041] Example 3

[0042] A magnetic spinel recyclable adsorbent, the preparation method of which is substantially the same as that of Example 1, except that:

[0043] In step (S2), FeMn2O4 magnetic adsorbent is obtained under an annealing temperature of 500°C.

[0044] Example 4

[0045] A magnetic spinel recyclable adsorbent, the preparation method of which is substantially the same as that of Example 1, except that:

[0046] In step (S2), FeMn2O4 magnetic adsorbent is obtained under an annealing temperature of 600°C.

[0047] Experimental Example 1 Structural Characterization of FeMn2O4 Magnetic Adsorbents Prepared in Each Example

[0048] The FeMn2O4 magnetic adsorbent prepared in Examples 1 to 4 was characterized by XRD. The specific results are as follows Figure 1 .

[0049] Depend on Figure 1 It can be seen that after the material was annealed at 300℃, 400℃, 500℃ and 600℃ in air, the diffraction peaks of the samples corresponded to the diffraction peaks of spinel FeMn2O4 (JCPDS card number: 75-0035). The 2θ values ​​of the diffraction peaks of 18.04°, 29.67°, 34.94°, 36.54°, 42.45°, 56.11° and 61.59° corresponded to the (111), (220), (311), (222), (400), (511) and (440) planes, respectively, confirming the formation of FeMn2O4. FeMn2O4 has a typical face-centered cubic lattice with a space group of Fdˉ3m and lattice constants of a=b=c=8.49nm; α=β=γ=90°. It can be seen that the lattice constant of FeMn2O4 is not affected by the change in temperature during annealing, indicating that annealing at different temperatures after preparation by co-precipitation will not change the crystal configuration of spinel. The ratio of trivalent iron to divalent iron in the spinel tetrahedron changes, and the higher the temperature, the higher the trivalent iron content.

[0050] Experimental Example 2 Study on the adsorption performance of FeMn2O4 magnetic adsorbents prepared in various embodiments

[0051] In order to study the antimony removal performance of FeMn2O4 prepared in the above embodiments, a series of antimony-containing solutions were prepared using SbCl3 solid as an antimony source, and the antimony removal performance of FeMn2O4 was tested at room temperature.

[0052] 1. Effect of FeMn2O4 at different annealing temperatures on the adsorption of Sb(Ⅲ)

[0053] 1) Adsorption capacity of FeMn2O4 for Sb(Ⅲ) at 300℃ annealing temperature

[0054] Under the conditions of initial Sb(Ⅲ) concentration of 100 mg / L and adsorbent concentration of 0.1 g / L, the pH was adjusted to 7 (±0.1). The mixture was placed in a 180 rpm shaker for reaction, and samples were taken at predetermined time intervals for a total of 240 min. The adsorbed solution was filtered through a 0.45 μm filter membrane and the concentration was determined using a flame atomic absorption spectrometer. The adsorption amount was measured to be 620.46 mg / g, and 91.02% of the adsorption equilibrium capacity could be reached within 20 min. The specific results are as follows: Figure 2 shown.

[0055] 2) Adsorption capacity of FeMn2O4 for Sb(Ⅲ) at 400℃ annealing temperature

[0056] Under the conditions of initial Sb(Ⅲ) concentration of 100 mg / L and adsorbent concentration of 0.1 g / L, the pH was adjusted to 7 (±0.1). The mixture was placed in a 180 rpm shaker for reaction, and samples were taken at predetermined time intervals for a total of 240 min. The adsorbed solution was filtered through a 0.45 μm filter membrane and the concentration was determined using a flame atomic absorption spectrometer. The adsorption capacity was measured to be 642.46 mg / g, and 98.23% of the adsorption equilibrium capacity could be reached within 20 min. The specific results are as follows: Figure 2 shown.

[0057] 3) Adsorption capacity of FeMn2O4 for Sb(Ⅲ) at 500℃ annealing temperature

[0058] Under the conditions of initial Sb(Ⅲ) concentration of 100 mg / L and adsorbent concentration of 0.1 g / L, the pH was adjusted to 7 (±0.1). The mixture was placed in a 180 rpm shaker for reaction, and samples were taken at predetermined time intervals for a total of 240 min. The adsorbed solution was filtered through a 0.45 μm filter membrane and the concentration was determined using a flame atomic absorption spectrometer. The adsorption amount was measured to be 698.81 mg / g, and 98.53% of the adsorption equilibrium capacity could be reached within 20 min. The specific results are as follows: Figure 2 shown.

[0059] 4) Adsorption capacity of FeMn2O4 for Sb(Ⅲ) at 600℃ annealing temperature

[0060] Under the conditions of initial Sb(Ⅲ) concentration of 100 mg / L and adsorbent concentration of 0.1 g / L, the pH was adjusted to 7 (±0.1). The mixture was placed in a 180 rpm shaker for reaction, and samples were taken at predetermined time intervals for a total of 240 min. The adsorbed solution was filtered through a 0.45 μm filter membrane and the concentration was determined using a flame atomic absorption spectrometer. The adsorption capacity was measured to be 891.31 mg / g, and 99.41% of the adsorption equilibrium capacity could be reached within 20 min. The specific results are as follows: Figure 2 shown.

[0061] Depend on Figure 2 It can be seen that the adsorption process of Sb(III) on the surface of the four FeMn2O4 mainly presents two stages. The first is the rapid adsorption process. Within 20 minutes, the FeMn2O4 of Examples 4 to 1 all showed a relatively fast rate of adsorption of Sb(III), and the adsorption capacity can reach 99.41%, 98.53%, 98.23% and 91.02% of the adsorption equilibrium capacity respectively, which also shows that the four FeMn2O4 have a strong time-effectiveness for the removal of Sb(III), and meet the conditions of 600℃FeMn2O4>500℃FeMn2O4>400℃FeMn2O4>300℃FeMn2O4. All samples basically reached equilibrium in 60 minutes. The adsorption amounts of Sb(III) of FeMn2O4 in Examples 4 to 1 when reaching adsorption equilibrium were 891.31 mg / g, 698.81 mg / g, 642.46 mg / g, and 620.46 mg / g, respectively. Compared with FeMn2O4 annealed at other temperatures, FeMn2O4 annealed at 600°C has a more ideal Sb(III) removal capability.

[0062] 5) Maximum adsorption capacity of FeMn2O4 annealed at 600℃ and fitting of Langmuir and Freundlich adsorption isotherm models

[0063] In order to study the removal effect of 600℃FeMn2O4 on Sb(III), the corresponding adsorption capacity of the synthesized samples was determined by adsorption isotherm experiment, and the adsorption behavior of Sb on FeMn2O4 annealed at 600℃ was analyzed.

[0064] 10 mg of FeMn2O4 material annealed at 600°C (FeMn2O4 of Example 4) was added to 460-620 mg / L (460, 480, 500, 520, 540, 560, 580, 600, 620 mg / L) Sb(III) solutions, respectively, and the pH was adjusted to 7 (±0.1) and then placed in a 180 rpm shaker for 5 hours to measure the Sb(III) concentration of the solution after adsorption. The statistical results are as follows: Figure 3 As shown (the horizontal axis is the equilibrium concentration of the adsorbate, and the vertical axis is the adsorption capacity).

[0065] In order to further understand the adsorption behavior of Sb(III) on FeMn2O4 annealed at 600℃, the Langmuir and Freundlich isotherm adsorption models were used to linearly fit the experimental data. The Langmuir model assumes that the adsorption process is uniform and the effect of the adsorbent on the adsorbate is a single-layer surface adsorption, while the Freundlich model is mainly used to describe the roughness of the adsorbent surface and multilayer adsorption.

[0066] Depend on Figure 3 It can be seen that the adsorption of Sb(III) by FeMn2O4 at 600℃ shows a strong adsorption capacity. The adsorption capacity increases with the initial concentration of Sb(III), and the adsorption capacity of FeMn2O4 increases accordingly. When the initial concentration reaches 580 mg / L, the adsorption capacity tends to be saturated, and the maximum adsorption capacity is 2674.49 mg / g. The Langmuir and Freundlich isotherm adsorption models are used to linearly fit the experimental data. According to the correlation coefficient R 2 It can be seen that the correlation coefficient R between the Langmuir model and the Freundlich model is 2 The Langmuir model is more suitable than the Freundlich model to describe the adsorption behavior of FeMn2O4 for Sb(III) removal at 600℃. The adsorption isotherm fitting results show that the adsorption process of FeMn2O4 on Sb(III) solution is more inclined to monolayer adsorption.

[0067] 2. Effect of different pH on the adsorption of Sb(Ⅲ) by FeMn2O4

[0068] A 600 mg / L Sb(III) solution was prepared, and 10 mg of FeMn2O4 material annealed at 600°C (FeMn2O4 of Example 4) was added. The pH was adjusted to 3-10, and then the mixture was placed in a shaker at 180 rpm for reaction for 5 hours and samples were taken to measure the concentration.

[0069] The statistical results can be found in Figure 4 .Depend on Figure 4It can be seen that when the pH is 4 or ≥7, the removal rate of Sb(Ⅲ) by FeMn2O4 reaches more than 90%, and under the condition of pH ≥ 7, the removal rate of Sb(Ⅲ) increases with the increase of pH value.

[0070] Experimental Example 3 Study on the Recyclability of FeMn2O4

[0071] Prepare 100mL of 600mg / L Sb(Ⅲ) solution, add 10mg of FeMn2O4 material annealed at 600℃ (FeMn2O4 of Example 4), adjust the pH to 7 (±0.1), place in a 180rpm shaker for 5 hours, take samples and measure the concentration. Recover the FeMn2O4 material using a magnet, rinse it repeatedly with deionized water 3 times, dry it, put it in 600mg / L Sb(Ⅲ) solution again for reaction, take samples and measure the concentration. Repeat this step twice and count the results.

[0072] The statistical results can be found in Figure 5 .Depend on Figure 5 It can be seen that after three cycles of reaction, 600℃FeMn2O4 can still effectively remove 600mg / L Sb(III) solution, and the third time can still remove 72.89% of Sb in the solution. 3+ . For Sb 3+ The difference in removal efficiency may be due to the fact that Sb was not completely washed away when the material was rinsed after each cycle experiment, and some Sb still remained on the FeMn2O4 surface to occupy the adsorption sites, as well as the influence of the presence of reactive attachments on the surface.

[0073] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A method for preparing a magnetic spinel recyclable adsorbent, characterized in that: The method comprises the following steps: (S1) the FeCl3 aqueous solution, the MnCl2 aqueous solution and the NaOH aqueous solution are fully mixed to form a suspension; (S2) placing the suspension obtained by mixing in step (S1) in a 97°C water bath and heating it for 120 min, repeatedly washing the obtained slurry with anhydrous ethanol and deionized water to remove residual alkaline substances, and drying the obtained particles in a vacuum drying oven at 100°C for 3 to 5 hours. After being fully ground, placing them in a tubular furnace, and annealing them at 300 to 600°C for 180 min at a heating rate of 10°C / min to obtain a FeMn2O4 magnetic adsorbent.

2. The preparation method according to claim 1, characterized in that: The concentration of the FeCl3 aqueous solution is 0.2 mol / L; the concentration of the MnCl2 aqueous solution is 0.4 mol / L; and the concentration of the NaOH aqueous solution is 4.29-10.00 mol / L.

3. The preparation method according to claim 1, characterized in that: The annealing temperature is 400-600°C.

4. The magnetic spinel recyclable adsorbent obtained by the preparation method according to claim 1.

5. The magnetic spinel recyclable adsorbent according to claim 4 is used for adsorbing Sb 3+ The application is characterized in that Under the condition of pH 4 or ≥7, the magnetic spinel recyclable adsorbent has good adsorption performance for Sb 3+ Adsorption.

6. The use according to claim 5, characterized in that: The adsorption time is 5 hours; or / and, the adsorption is carried out on a shaking table at 180 rpm; Or / and, the adsorption is carried out at room temperature.

7. The use according to claim 5, characterized in that: The adsorption is carried out at a pH of 4, 7, 8, 9 or 10.

8. The use according to claim 5, characterized in that: The Sb 3+ The initial concentration is 460~620mg / L.

9. The use according to claim 8, characterized in that: The Sb 3+ The initial concentration was 600 mg / L.

10. The use according to claim 5, characterized in that: The magnetic spinel recyclable adsorbent is recovered by a magnet, repeatedly rinsed with deionized water, dried, and reused.

Citation Information

Cited By

  • Preparation method and application of magnetic porous ceramsite

    CN121060455A